DEMOKRASI EKONOMI PADA KEBIJAKAN HAK KONSESI PELABUHAN DI INDONESIA DAMPAK DEMONOPOLISASI PT.PELINDO (PERSERO) - Putu Samawati Saleh; Wahyu Ernaningsih; Suci Falmbonita (Faculty of Law, Tanjungpura University, 2023)
AbstractThe demonopolization policy towards PT.Pelindo (Persero) through Law No.17 Year 2008 concerning Shipping, is carried out by the government based on the demands of globalization in order to create perfect competitive market conditions, efficiency and effectiveness in corporate management. Demonopolization has an impact on the change in the status of PT. Pelindo (Persero), which was previously a regulator and operator by monopolizing port business activities, and become a port operator in the format of a Port Business Enterprise (PBE). As PBE PT.Pelindo (Persero) has the same status as a Private PBE, where the exploitation of ports is done through concession rights granted by the Port Authority (PA). The fundamental issue is to examine whether the concession rights which are the impact of demonopolization are in line with the concept of economic democracy based on the Indonesian constitution. The study was conducted using a normative juridical research method and a legislative approach. The results of the study are anticipatory strategies that can be considered by the government in determining policies that prioritize the principles of democracy economy in accordance with the Constitution of the Republic of Indonesia. Determination of the choice to determine the granting of the port concession rights to the private sector must be able to be decided on carefully consideration. The most important thing is to ensure that the economic democratic system must be able to be implemented in the performance of ports even though managed by the private sector, not to override the protection function of the lives of many people in order to achieve the demands of the maximum profit of the company.AbstrakKebijakan demonopolisasi terhadap PT.Pelindo (Persero) melalui Undang-undang No.17 Tahun 2008 tentang Pelayaran, dilakukan oleh pemerintah atas dasar tuntutan globalisasi demi menciptakan kondisi pasar persaingan sempurna, efisiensi serta efektifitas dalam pengelolaan korporasi. Demonopolisasi berdampak pada perubahan status PT.Pelindo (Persero) yang semula berkedudukan sebagai regolator dan operator dengan memonopoli kegiatan usaha kepelabuhanan, berubah hanya menjadi operator pelabuhan dalam format Badan Usaha Pelabuhan (BUP). Sebagai BUP PT.Pelindo (Persero) memiliki status yang sama dengan BUP Swasta, dimana pengusahaan atas pelabuhan dilakukan melalui hak konsesi yang diberikan oleh Otoritas Pelabuhan. Persoalan mendasar yang menjadi bahasan dalam artikel ini adalah untuk menguji apakah hak konsesi yang merupakan dampak dari demonopolisasi sejalan dengan konsep demokrasi ekonomi berdasarkan konstitusi Indonesia. Kajian dilakukanlah dengan menggunakan metode penelitian yuridis normatif dan pendekatan perundang-undangan. Hasil penelitian berupa strategi antisipasi yang dapat dipertimbangkan oleh pemerintah dalam menentukan kebijakan yang mengutamakaprinsip-prinsip perekonomian kerakyatan sesuai dengan Konstitusi Republik Indonesia. Penentuan pilihan untuk menetapkan pemberian hak konsesi pelabuhan kepada swasta harus mampu diputuskan dengan dasar pertimbangan yang kuat. Hal terpenting adalah memastikan bahwa sistem demokrasi ekonomi harus mampu diterapkan dalam pelaksanaan kinerja pelabuhan meskipun dikelola oleh swasta, jangan sampai mengenyampingkan fungsi perlindungan akan hajat hidup orang banyak demi mencapai tuntutan keuntungan maksimal perusahaan.